Guest Loyalty Programs of Chain Hotels: The Case of Turkey - Güzel, Ramazan; Oktay, Kutay; Orynbaeva, Ultugan (University of International Business, 2023)
The increasing competition among companies has forced them to adopt new marketing methods and develop new strategies to retain customers. One such strategy is the use of loyalty program cards, which were initially used as a benefits program but have now become a popular marketing strategy used by many hotel chains in Turkey. Loyalty programs are designed to encourage customers to continue using a company's services or products by offering rewards, discounts, and other privileged services. This study aims to conduct a content analysis of the websites of 10 hotels in Turkey to explore the facilities these hotels offer through their loyalty programs. The content analysis focuses on the services offered by these hotels, which are designed to retain customer loyalty. The data was collected by visiting the websites of the selected hotels and analyzing the content using the content analysis method. The findings were presented descriptively, highlighting the similarities and differences between the services offered by the hotels under the name of the loyalty program. The study found that the loyalty programs offered by hotel chains in Turkey have both common and different characteristics. Overall, this study provides valuable insights into the loyalty programs offered by international hotel chains in Turkey. By analyzing the content of the websites, the study highlights the key facilities offered by these hotels to retain customer loyalty. The findings of this study could be useful to hotel managers and marketers in designing effective loyalty programs that meet the needs and expectations of their customers.